Improvement of Alpha-amylase Activity from Bacillus Licheniformis using UV Radiation and Modified Media Composition - Khatun, M Mahfuza; Zarin, Farahdiba; Tasnim, Kazi Zarin; Sarmin, Fahria (Bioresearch Communications, 2023)
Alpha-amylases are glycosidic bond hydrolyzing enzymes produced in many microorganisms. In the modern era, the spectrum of amylase applications has expanded into various industries, including medical fields. Among other approaches, strain improvement by mutation and culture optimization are attractive methods for increasing the productivity of alpha-amylase in bacterial strains. The present study aimed at enhancing the yield of the enzyme alpha-amylase from the host strain Bacillus licheniformis. The UV irradiation has been used to induce mutations in the bacterial strain with different time durations. Afterwards, the mutant strains were cultured in different modified growth media for enzyme production. Among the four time periods,the highest enzyme activity (705.23 U/ml) was observed after 24 hours which is more than two-fold higher compared to the enzyme activity of the host stain (345.31 U/ml). In addition, enzyme yield varied significantly in modified culture media (i.e, MP1 and MP2, MP3 and MP4) with different carbon and nitrogen compositions. The mutant strain cultured in MP3 medium had the highest amylase activity which was 1461.2 U/ml at 24 hours. More interestingly, this medium also had the highest enzyme activity (1080.5 U/ml) at 48 hours. The trend of enzyme activity showed a decreasing tendency when the strains cultured in MP1, MP2, and MP3 media, but exceptionally, a sharp decreasing trend was seen in MP4 media from 622.1 U/ml at 24 hours to 428.4 U/ml at 48 hours. From the findings, it can be concluded that B. licheniformis is a good candidate to employ for alpha-amylase production in a modified MP3 culture condition for a short time. However, other limiting factors need to be considered for increasing the yield. Bioresearch Commu. 9(2): 1351-1356, 2023 (July)